Activation of Immune Genes in Leafhoppers by Phytoplasmas and Symbiotic Bacteria - Gonella, Elena; Mandrioli, Mauro; Tedeschi, Rosemarie; Crotti, Elena; Pontini, Marianna; Alma, Alberto (Frontiers in Physiology, 2019)
Insect immunity is a crucial process in interactions between host and microorganisms; presence of pathogenic, commensal, or beneficial bacteria may result in different immune responses. In Hemiptera vectors of phytoplasmas, infected insects are amenable to carrying high loads of phytopathogens, besides hosting other bacterial affiliates, which have evolved different strategies to be retained; adaptation to host response and immunomodulation are key aspects of insect-symbiont interactions. Most of the analyses published to date have investigated insect immune response to pathogens, whereas few studies have focused on the role of host immunity in microbiota homeostasis and vectorial capacity. Here the expression of immune genes in the leafhopper vector of phytoplasmas Euscelidius variegatus was investigated following exposure to Asaia symbiotic bacteria, previously demonstrated to affect phytoplasma acquisition by leafhoppers. The expression of four genes related to major components of immunity was measured, i.e. defensin, phenoloxidase, kazal type 1 serine protease inhibitor and Raf, a component of the Ras/Raf pathway. The response was separately tested in whole insects, midguts and cultured hemocytes. Healthy individuals were assessed along with specimens undergoing early- and late-stage phytoplasma infection. In addition, the adhesion grade of Asaia strains was examined to assess whether symbionts could establish a physical barrier against phytoplasma colonization. Our results revealed a specific activation of Raf in midguts after double infection by Asaia and flavescence dorée phytoplasma. Increased expression was observed already in early stages of phytoplasma colonization. Gut-specific localization and timing of Raf activation are consistent with the role played by Asaia in limiting phytoplasma acquisition by E. variegatus, supporting the involvement of this gene in the anti-pathogen activity. However, limited attachment capability was found for Asaia under in vitro experimental conditions, suggesting a minor contribution of physical phytoplasma exclusion from the vector gut wall. By providing evidence of immune modulation played by Asaia, these results contribute to elucidating the molecular mechanisms regulating interference with phytoplasma infection in E. variegatus. The involvement of Raf suggests that in the presence of reduced immunity (reported in Hemipterans), immune genes can be differently regulated and recruited to play additional functions, generally played by genes lost by hemipterans